2010
DOI: 10.1021/bi1012436
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Crystal Structures of Streptococcus pneumoniae Nicotinamidase with Trapped Intermediates Provide Insights into the Catalytic Mechanism and Inhibition by Aldehydes,

Abstract: Nicotinamidases are salvage enzymes that convert nicotinamide to nicotinic acid. These enzymes are essential for the recycling of nicotinamide into NAD+ in most prokaryotes, most single cell and multicellular eukaryotes, but not in mammals. The significance of these enzymes for nicotinamide salvage and for NAD+ homeostasis has increased interest in nicotinamidases as possible antibiotic targets. Nicotinamidases are also regulators of intracellular nicotinamide concentrations, thereby regulating signaling of do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
71
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(81 citation statements)
references
References 56 publications
10
71
0
Order By: Relevance
“…In addition to the covalent linkage to C167, nicotinaldehyde is ligated to the active-site zinc through the pyridine ring nitrogen (Figure 1). This zinc ligation is consistent with recent structures of nicotinamidases from Acinetobacter baumanii and Streptococcus pneumoniae (31, 52). The active-site zinc is also ligated by D51, H53, and H94, consistent with the previous S. cerevisiae Pnc1 apo-structure (32).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In addition to the covalent linkage to C167, nicotinaldehyde is ligated to the active-site zinc through the pyridine ring nitrogen (Figure 1). This zinc ligation is consistent with recent structures of nicotinamidases from Acinetobacter baumanii and Streptococcus pneumoniae (31, 52). The active-site zinc is also ligated by D51, H53, and H94, consistent with the previous S. cerevisiae Pnc1 apo-structure (32).…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, we observed evidence for two water molecules that also coordinate the zinc; one of these is within hydrogen bonding distance of one conformation of E129 (E129 is present in two conformations in the structure) (Figure 1C). The carbonyl oxygen of nicotinaldehyde forms hydrogen bonds to the backbone amide nitrogens of A163 and C167 consistent with recent structures of S. pneumoniae PncA (52). The pyridine ring of nicotinaldehyde is also bound within an aromatic cage consisting of F13, W91, Y131, and Y166 (Figure 1B).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…HL-48 (UniProt code: A0A0P7YXE9). In addition, PolyNic also showed variable similarity (25–46%, Supplementary Table S1) with the crystallized nicotinamidases found in the bibliography ( Figure 5 ) (Du et al, 2001; Hu et al, 2007; Fyfe et al, 2009; French et al, 2010a; Gazanion et al, 2011; Liu et al, 2011; Petrella et al, 2011). …”
Section: Resultsmentioning
confidence: 83%
“…S2). The kinetic parameters of nicotinamidase have been studied in different bacteria (Mycobacterium tuberculosis [17], Streptococcus pneumoniae [18], and Oceanobacillus iheyensis [16]), archaea (Acidilobus saccharovorans [19]), and eukaryotes (Saccharomyces cerevisiae [12]). The kinetic parameters determined in this study are comparable to those of nicotinamidases previously reported from other organisms ( Table 1).…”
mentioning
confidence: 99%